Effect of melatonin, zinc sulfate, nano-melatonin, and nano-zinc oxide on mitochondria function and developmental competence of buffalo oocytes (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The aim of the current work is studying the effect of antioxidants and nano-antioxidants on in vitro development and mitochondrial function of buffalo oocytes. Materials and Methods: Good and excellent Buffalo oocytes were in vitro matured: (1) tissue culture medium-199 (control group), (2) TCM-199 + melatonin (Mel) 10−9 M (Mel group), (3) TCM-199 + zinc 10−6 M (Zn group), (4) TCM-199 + nano- Mel 10−6 M (N-Mel group), and (5) TCM199 + nano-zinc-oxide 10−6 M (N-ZnO group) and incubated with CO2 5% and 38.5°C for 22 hr. In vitro-matured oocytes were either stained for mitochondrial function or cultured for detection of embryo development. Results: The maturation rate of buffalo oocytes in the N-Mel and N-ZnO groups had a significant (p < 0.05) increase (91.89% and 93.64%, respectively) compared to the Mel group (85.78%) and Zn group (81.37%), and all groups were significantly higher than the control (73.16%). Mitochondrial intensity was significantly elevated (p < 0.05) in the N-Mel and N-ZnO groups than in oocytes matured in the Mel, Zn, or control groups. Rates of fertilization, cleavage, and transferable embryos of buffalo oocytes matured in vitro were significantly raised in the N-ZnO group (88.35%, 85.93%, and 30.71%, respectively) and the N-Mel group (86.74%, 82.75%, and 28.32%, respectively) (p < 0.05) when compared with the Mel group (82.46%, 77.25%, and 21.29%, respectively) and the Zn group (79.98%, 75.19%, and 19.68%, respectively), and all were increased significantly (p < 0.05) compared to the control group (71.76%, 68.7%, and 11.98%, respectively). Conclusion: Supplementation of maturation medium with Mel 10−9 M and zinc sulfate 10−6 M and nano-Mel 10−6 M and nano-zinc oxide 10−6 M improves buffalo oocyte maturation rates, mitochondrial function, and embryo development.J. Adv. Vet. Anim. Res., 11(4): 1093–1104, December 2024http://doi.org/10.5455/javar.2024.k860